Analysis of Porcine Model of Fecal-Induced Peritonitis Reveals the Tropism of Blood Microbiome - Hyun, Hwi; Lee, Min Seok; Park, Inwon; Ko, Hwa Soo; Yun, Seongmin; Jang, Dong-Hyun; Kim, Seonghye; Kim, Hajin; Kang, Joo H.; Lee, Jae Hyuk; Kwon, Taejoon (Frontiers in Cellular and Infection Microbiology, 2021)
Recent studies have proposed the existence of a blood microbiome, even in the healthy host. However, we do not know how the blood microbiome changes when a bloodstream infection (BSI) occurs. Here, we analyzed the dynamics of the blood microbiome in a porcine model of polymicrobial bacteremia induced by fecal peritonitis. The bacterial populations in the blood microbiome were retained throughout the experimental period. However, there were significant taxonomic differences between the profile in the fecal and blood microbiomes, reflecting tropism for the blood environment. We also noted a slight increase in Bacteroidetes, which is a major component of the gut microbiome, as sepsis developed. Comparison of the functional pathways in the blood and fecal microbiomes revealed upregulation of pathways involved in environmental interactions, and downregulation of those related to cell proliferation, in the former. Based on the enriched biological pathways, we concluded that communication and stress management pathways are essential for the survival of the blood microbiome under harsh conditions. This study suggests that the microbiota can be stably retained in the bloodstream over time.